PERAN AI DALAM KEHIDUPAN MODERN: STUDI KASUS DI PENDIDIKAN, RUMAH TANGGA, DAN DUNIA KERJA - Nurkholis, Muhammad; Wardhani, Dyah Febria (Journal of Information System, Informatics and Computing, 2025)
Artificial Intelligence (AI) has become an integral part of daily life, including in the fields of education, household management, and the workplace. This study aims to analyze the role of AI in enhancing the efficiency and effectiveness of human activities within the contexts of education, household management, and employment, as well as to identify the challenges associated with its implementation. The methodology used in this research includes literature review and interviews with individuals who have direct experience in utilizing AI in education, household, and professional settings. The results show that AI supports the learning process by providing broader access to educational materials and personalizing learning methods. In households, AI contributes to the automation of domestic tasks and financial management, while in the workplace, AI enhances operational efficiency and enables automation of various administrative tasks. However, several challenges emerge, including limited digital literacy, concerns over workforce reduction, and ethical issues related to the use of personal data. In conclusion, AI plays a significant role in improving human quality of life across various aspects, but appropriate regulations and policies are needed to ensure that its utilization brings maximum benefit to society.